1976
DOI: 10.1002/prac.19763180103
|View full text |Cite
|
Sign up to set email alerts
|

Reactions with Thiazolo[3,2‐b]‐s‐triazol‐3(2H)‐ones

Abstract: 5‐Aryl‐3‐carboxymethylthio‐1,2,4‐triazoles 2 are cyclised to 6‐arylthiazolo[3,2‐b]‐s‐triazol‐3(2H)‐ones 3. This structural assignment has been based on IR and NMR spectra. 2‐Arylmethylene‐6‐arylthiazolo[3,2‐b]‐s‐triazol‐3(2H)‐ones 7 were prepared by several methods. Compounds 3 coupled with diazotised anilines to give 2,3‐dihydro‐6‐arylthiazolo[3,2‐b]‐s‐triazole‐2,3‐dione 2‐arylhydrazones 8. The action of amines on 3a opens the thiazolone ring with the formation of substituted (5‐phenyltriazol‐3‐ylthio)‐acetam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1976
1976
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The structures of the isolated compounds were determined by IR, 1 H-NMR spectral data, X-ray crystallographic and elementary analysis. The compounds 4−6 and 8 have already been synthesized by Ali et al[19] and anti-inflammatory activities of these compounds have not been reported. Conjugate additions of cyclic sec.…”
mentioning
confidence: 99%
“…The structures of the isolated compounds were determined by IR, 1 H-NMR spectral data, X-ray crystallographic and elementary analysis. The compounds 4−6 and 8 have already been synthesized by Ali et al[19] and anti-inflammatory activities of these compounds have not been reported. Conjugate additions of cyclic sec.…”
mentioning
confidence: 99%
“…Hybrid methods in which steam and solvent are co-injected have been suggested to overcome some of the limitations of each method. Several studies, including Ali and Abad, [1] Redford and McKay, [2] Redford, [3] Shu and Hartman, [4] Sarma et al, [5] Nasr et al, [6] Nasr and Ayodele, [7] Ayodele et al, [8] McCormack, [9] and Mohammadzadeh et al [10] have investigated the co-injection of solvent and steam for the recovery of heavy oil and bitumen.…”
Section: Introductionmentioning
confidence: 99%
“…This carbonyl frequency is rather high; however, it has been noted that a carbonyl group attached to a triazole and a triazine rings shows unusually high stretching frequency [5][6][7][8] . The NMR spectrum (DMSO-d6) of 3 a, shows a methylene group (s, 2H) at r 5.27 ppm.…”
Section: Hn^^n Rmentioning
confidence: 99%